Monopoly, inequality and redistribution via the public provision of private goods - Margarita Katsimi; Thomas Moutos (Center for Economic Studies and ifo Institute (CESifo), 2004)
The relationship between inequality and redistribution is usually studied under the assumption that the government collects different amounts of taxes from each citizen (voter) but gives back the same amount (in cash or in kind) to everyone. In this paper we consider what happens if the government can redistribute through both sides of its budget (revenue and expenditure). We study the effects of inequality on the size (and structure) of redistributive programs in both perfectly competitive and monopolistic settings. We find that the presence of monopoly results in a higher tax rate than in the competitive case and that in the latter case an increase in inequality can be associated with a fall in the tax rate. We find also that although the median voter may not vote for a positive tax rate in the presence of public sector inefficiency under perfect competition, she may prefer – ceteris paribus – a positive tax rate in the presence of monopoly.
Keywords: P16; H42; H23; 330; monopoly; redistribution; inequality; public goods; median voter; Einkommensumverteilung; Median Voter; Einkommensverteilung; Steuerpolitik; Monopol; Theorie